PERMINTAAN DAGING SAPI DI KOTA BANJARMASIN - MUNAWARAH MUNAWARAH (PPJP Universitas Lambung Mangkurat, 2019)
This study aims to discovery out how the beef price, the broiler price, the price of gabus fish, the price of salty telang fish and percapita income with influence demand of beef at banjarmasin city and what the factor is the most dominant affect of beef at Banjarmasin city.The study used data during six years from 2010 untill 2015 years in a matter of the monthly. this study used analyze technic regresi linear double with variabel devenden demand of beef(Y) and variabel independen price of beef(X1) price of broiler (X2) ,price of gabus fish (X3), price of salty telang fish (X4) and percapita income (X5). from this study result variabel price salty telang fish influential significate to demand of beef at banjarmasin city and variabel beef price, broiler price,gabus fish price and percapita income with all not influential significate to face demand of beef at Banjarmasin City. The factor the most dominant demand of beef is variabel the salty telang fish. Keywords : Demand of beef, the beef price, the broiler price, the gabus fish price, the price salty telang fish and percapita income.